Herpes Simplex Virus 1 Induces Microglia Gasdermin D-Dependent Pyroptosis Through Activating the NLR Family Pyrin Domain Containing 3 Inflammasome - Hu, Xiao; Zeng, Qiongzhen; Xiao, Ji; Qin, Shurong; Wang, Yuan; Shan, Tianhao; Hu, Di; Zhu, Yexuan; Liu, Kaisheng; Zheng, Kai; Wang, Yifei; Ren, Zhe (Frontiers in Microbiology, 2022)
Herpes simplex virus type 1 (HSV-1) is a highly prevalent virus in humans and cause severe forms of inflammation, such as herpes simplex encephalitis (HSE). Pyroptosis is a new type of inflammatory cell death triggered by inflammasome and caspase-1 activation. Nonetheless, mechanisms by which HSV-1 induces encephalitis and cell-death are far from being understood. In this study, we confirmed for the first time that the DNA virus HSV-1 triggers Gasdermin D-dependent pyroptosis by activating NLRP3 inflammasomes in mouse microglia, leading to mature IL-1β production and active caspase-1 (p10) release. Inhibition of microglial NLRP3 inflammasome activation suppressed HSV-1-induce Gasdermin D-dependent pyroptosis. In addition, NLRP3 and IL-1β expression levels were significantly increased in mouse model of herpes simplex encephalitis compared with normal mice without viral infection. Collectively, our data revealed that the activation of inflammasomes and GSDMD-dependent pyroptosis is the mechanism of HSV-1 inducing inflammation and provides treatment targets for viral inflammation.